Induction motor control and speed estimation via adaptive and artificial intelligence method - Kamenko Ilija; Nikolić Perica; Matić Dragan; Bugarski Vladimir (Journal on Processing and Energy in Agriculture, 2011)
This paper shows the optimization of the parameters of PI controllers in the application of vector control of a three-phase induction motor by genetic algorithm for the set optimality criterion. There is also the projecting procedure as well as the comparative analysis of the performances of speed estimator based on MRAS observer and speed estimator based on ANN. The basis of the research is a mathematical model of vector control of a three-phase induction motor, which was developed in MATLAB/Simulink. The experimental analysis of the results was carried on the laboratory model of electric motor drive based on the dSPACE card. The application of the encoder provides a smaller measurement error, whereas the application of estimators is possible in the cases for which pinpoint accuracy is not required and for which the price and/or reliability are of greater interest.